A Near-Zero Energy Smart Greenhouse Integrated Into a Microgrid for Sustainable Energy and Microclimate Management - Tuan Minh Tran; Ahmed Ouammi; Louis A-Dessaint (IEEE Access)
This paper presents a novel smart greenhouse integrated into a microgrid (SGIM) designed to optimize energy and microclimate management for sustainable agriculture. The SGIM integrates photovoltaic (PV) panels, a micro-combined heat and power (micro-CHP) unit, and an energy storage system to deliver efficient, localized energy generation and management. Within this framework, a Nonlinear Model Predictive Control (NMPC) and an Extended Kalman Filter (EKF) are employed to regulate critical microclimate parameters such as temperature, relative humidity, CO2 concentration, and lighting intensity, while optimally managing energy storage to reduce grid power imports. The NMPC minimizes a cost function encompassing multiple objectives and constraints, whereas the EKF enhances control precision by addressing measurement errors and model noise. Simulations revealed that the SGIM met over 83% of its energy needs through local generation, with only 3.8% sourced from the external grid. This approach offers an effective solution for achieving near-zero energy consumption in sustainable agriculture, with scalability for various greenhouse types and sizes.